THz molecular science in condensed phases - Tominaga, Keisuke (2020)
We investigated the charge carrier dynamics of benzoporphrin (BP) and BP-based bulk heterojunction thin films by using time-resolved THz spectroscopy [8, 9]. In both samples, we observed instantaneous appearance of transient THz signals, which are attributed to mobile charge carriers.